The Impact of Economic Freedom on the Economic Complexity of Trade in Indonesia - Cut Syazalisma; Suriani Suriani; M. Shabri Abd. Majid (Grimsa Journal of Business and Economics Studies, 2026)
This study investigates the impact of economic freedom on the economic complexity of trade in Indonesia, an issue that is increasingly relevant for understanding structural transformation in resource-dependent economies. While the existing literature has separately examined the role of economic freedom in promoting growth and the importance of economic complexity for development, limited attention has been given to how economic freedom influences the sophistication and diversification of exports, particularly in the Indonesian context. Using annual data from 1998 to 2024, this study employs the Economic Complexity Index as the dependent variable and the Economic Freedom Index as the main independent variable, with GDP per capita, FDI inflows, and trade openness included as control variables. The analysis applies Robust Least Squares method, incorporating M-estimation, S-estimation, and MM-estimation techniques to ensure the robustness of the results. The findings reveal that economic freedom has a negative and statistically significant effect on economic complexity, suggesting that liberalization may reinforce specialization in low-complexity, resource-based sectors rather than promote export diversification. In contrast, GDP per capita positively influences economic complexity, while FDI inflows and trade openness do not exhibit significant effects. These results indicate that external integration and market liberalization alone are insufficient to enhance export sophistication without supportive domestic structural conditions. This study highlights the need for policymakers to complement market-oriented reforms with targeted industrial and institutional policies that promote economic diversification, capability accumulation, and technological upgrading to enhance export sophistication.